New polyols with isocyanuric structure by thiol-ene "click" chemistry reactions. (November 2017) - Gupta, Ram K; Ionescu, M; Wan, X; Radojcic, D; Bilic, N
New polyols with isocyanuric structure were synthesized by thiol-ene "click" chemistry of triallyl isocyanurate with 1-thioglycerol and 2-mercaptoethanol. The synthesized polyols, prepared with high reaction rates and in very high yields, were chemically and structurally characterized. These polyols were used for the preparation of rigid polyurethane foams with excellent physical–mechanical properties and inherent flame retardancy. By alkoxylation of isocyanuric polyols with propylene oxide and/or ethylene oxide in a self-catalytic process, odorless polyols with lower hydroxyl numbers and lower viscosities were obtained, leading to PU foams with good properties, but without inherent flame retardancy. The synthesized polyols with isocyanuric structure are suitable for the preparation of all types of rigid polyurethane foams, including thermoinsulation of freezers, buildings, storage tanks and pipes for the food and chemical industry, for packaging, and as wood substitutes.